2022
DOI: 10.1002/smll.202203173
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activities in Alkaline Hydrogen and Oxygen Evolution Reactions on MoS2 Electrocatalysts by In‐Plane Sulfur Defects Coupled with Transition Metal Doping

Abstract: Abstract2D transition metal disulfides (TMDs) are promising and cost‐effective alternatives to noble‐metal‐based catalysts for hydrogen production. Activation of the inert basal plane of TMDs is crucial to improving the catalytic efficiency. Herein, introduction of in‐plane sulfur vacancies (Sv) and 3d transition metal dopants in concert activates the basal planes of MoS2 (M‐Sv‐MoS2) to achieve high activities in the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Acetate introducing mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…1,2 Due to the high combustion caloric value, sustainability and zero carbon dioxide emission, hydrogen (H 2 ) is considered as a promising alternative to fossil fuels. 3 Electricity-driven water dissociation represents one of the most promising and appealing approaches for the manufacture of high-purity oxygen and hydrogen, deriving from the oxygen evolution reaction (OER) at the anode and hydrogen evolution reaction (HER) at the cathode. 4,5 Until now, the main obstacles restricting the wide commercial application of water electrolysis devices are the lack of highly active and low-cost electrocatalysts, which contribute to low overpotential requirements for both HER and OER processes.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Due to the high combustion caloric value, sustainability and zero carbon dioxide emission, hydrogen (H 2 ) is considered as a promising alternative to fossil fuels. 3 Electricity-driven water dissociation represents one of the most promising and appealing approaches for the manufacture of high-purity oxygen and hydrogen, deriving from the oxygen evolution reaction (OER) at the anode and hydrogen evolution reaction (HER) at the cathode. 4,5 Until now, the main obstacles restricting the wide commercial application of water electrolysis devices are the lack of highly active and low-cost electrocatalysts, which contribute to low overpotential requirements for both HER and OER processes.…”
Section: Introductionmentioning
confidence: 99%
“…It can be clearly observed that there is an obvious response to the oxygen evolution reaction process for the S-NiFeV LDH electrode in 1.0 M KOH solution without urea, which originates from the oxidation peak of the Ni species (Ni 2+ /Ni 3+ ). [54][55][56][57] Depicted in Fig. 5 It is evident that the elaborate S-NiFeV LDH demonstrates a significantly improved UOR performance with a low onset potential of 1.34 V (vs. RHE), beyond which a dramatic increase in current density is determined.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…It can be clearly observed that there is an obvious response to the oxygen evolution reaction process for the S-NiFeV LDH electrode in 1.0 M KOH solution without urea, which originates from the oxidation peak of the Ni species (Ni 2+ /Ni 3+ ). [54][55][56][57] Depicted in Fig. 5(b) are the LSV curves of the S-NiFeV LDH, NiFeV LDH, and NiFe LDH for the UOR, along with those of the commercial RuO 2 and bare NF as a contrast.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…10,11 Currently, it has been shown that Pt and RuO 2 / IrO 2 are superior catalysts, but at the same time, there is the problem of high price due to the scarcity of the earth's reserves. 12,13 Therefore, high activity and low-cost catalysts are crucial for the long term development of water electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Overuse of fossil energy is increasing climate change and energy security concerns, and countries around the world are seeking to promote energy change and green development through vigorous development of clean energy methods. Thanks to its high specific energy density, excellent conversion efficiency, and the cleanest combustion products, hydrogen energy has unparalleled advantages as an alternative energy source. Electrolytic hydrogen production is a technology that uses water as the raw material to electrochemically process water into hydrogen and oxygen. The method is simple and efficient, with high purity of the prepared hydrogen, and the whole process is green and environmentally friendly. , However, the high reaction energy barriers of the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode require catalysts to resolve. , Currently, it has been shown that Pt and RuO 2 /IrO 2 are superior catalysts, but at the same time, there is the problem of high price due to the scarcity of the earth’s reserves. , Therefore, high activity and low-cost catalysts are crucial for the long term development of water electrolysis.…”
Section: Introductionmentioning
confidence: 99%